Soft-tissue fixation is not inferior to suture-anchor fixation in reconstruction of the medial patellofemoral ligament using a nonresorbable suture tape - Zimmermann, Felix; Schonhoff, Mareike; Jäger, Sebastian; Milinkovic, Danko Dan; Franke, Jochen; Grützner, Paul Alfred; Balcarek, Peter J.; Vetter, Sven Y. (Knee surgery, sports traumatology, arthroscopy, 2023)
Reconstruction of the medial patellofemoral ligament (MPFL-R) with nonresorbable suture tape (FiberTape®, FT) is becoming popular. Patella-side fixation of the FT can be performed with suture anchors or via soft-tissue fixation. The aim of this study was to investigate whether patella-side soft-tissue fixation can achieve equivalent primary stability compared to suture-anchor fixation.
Online veröffentlicht am 22. August 2022
Gesehen am 04.05.2023